First report of Halimeda magnicuneata Verbruggen & Dumilag 2020 from the northern coast of Sri Lanka - Anjalie, Narasinghe Mudiyanselage Ishara; Krishnapillai, Nahmagal; Kuganathan, Sivashanthini (Journal of Fisheries, 2025)
The genus Halimeda is a group of calcifying green algae that play a crucial role in sediment production and reef stabilisation. During a field survey in November–December in Mathagal, Northern Sri Lanka, the previously unreported species Halimeda magnicuneata was identified. This marks the first record of the species in Sri Lankan waters and was confirmed through morphological analysis, segment cross-sections and comparisons with established taxonomic descriptions. The collected specimens had segment widths of 8–21 mm (mean 13.1±4.6 mm), lengths of 9–17 mm (mean 9.9±3.8 mm) and thicknesses of 0.50–1.25 mm (mean 0.75±0.31 mm). The holdfast measured 4–8 mm (mean 6.17±2.02 mm), with an overall algal height of 95–110 mm (mean 102.3±7.51 mm). The branching pattern was dichotomous, a typical characteristic of the genus. The species was found attached to coral rubble in shallow waters ( 3 m depth). The microscopic view of segment surface showed hexagonal cells with thick cell walls and cross-section of segment revealed medulla and cortex which consists of layers of primary and inflated secondary utricles. These microscopic characteristics further authenticated the species identification. The present finding contributes to the growing knowledge of the region’s marine biodiversity and highlights the importance of continuous biodiversity assessments. The documentation of H. magnicuneata underscores the need for further studies on its ecological interactions, distribution patterns and response to environmental changes.